How do land use regulations influence industrial land prices? Evidence from China - Tu, Fan; Zou, Shuangling; Ding, Ran (International Journal of Strategic Property Management, 2021)
Due to low industrial land prices and inefficiently used industrial land, China’s central government has reformed land regulations in order to promote more market-oriented industrial land. Considering the differences in land management between developed and developing countries, this study aims to investigate the impact of land use regulations on industrial land prices in China and the effect of market-oriented reforms of industrial land policy. Measures that capture multiple dimensions of land use regulation tools are incorporated into OLS models based on a micro dataset from 1999 to 2016 that covers Jiaxing City in Eastern China. The results show that (1) The land policy implemented in 2006 to promote industrial land marketization has had a very limited effect; (2) The impact of land supply on industrial land prices was decreased for land transferred through listings after 2006, which implies an immature marketization; (3) Zoning instruments has obvious effects on industrial land prices; (4) The results imply that the effect of land use regulations varies with firm ownership and development zones. The findings in this paper clearly show that the industrial land market should be more open and competitive and combined with a rational land supply to promote the market-oriented price mechanism.First published online 28 December 2020